An architecture of a query evaluation system for deductive databases - Ali Mamat, (Universiti Kebangsaan Malaysia, 1996)
The technology of deductive database is now mature enough due to the considerable research efforts that have been made on the field for the last ten years. This achievement is demonstrated by the emergence of efficient and easy to use systems with their capability of supporting a declarative, rule based style of expressing queries and applications on databases. This paper describes an overview of architecture of a query evaluation system for deductive databases that has been developed.